1990
DOI: 10.1177/000331979004100507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin on Vasoconstrictor Responses to Alpha Agonist and Tilting

Abstract: The effects of insulin on vasoconstrictor response were studied in diabetics without autonomic neuropathy. Vasoconstrictor response to phenylephrine was measured before and after insulin injection in 10 diabetics. Mean blood pressure, forearm blood flow, and forearm vascular resistance remained unchanged after insulin administration. But the increase in forearm vascular resistance to phenylephrine decreased significantly and heart rate increased significantly after insulin injection. In 9 diabetics, vasoconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Similar results have subsequently been obtained by other investigators (3)(4)(5). This was associated with a decrease in forearm vascular resistance.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Similar results have subsequently been obtained by other investigators (3)(4)(5). This was associated with a decrease in forearm vascular resistance.…”
supporting
confidence: 90%
“…This is indicated by the smaller increase and the paradoxical decrease in FVRs in the standing position after subcutaneous insulin, in subjects without and with AN, respectively (Fig. What is new in this compared with previous studies (1)(2)(3)(4)(5) is that a relevant decrease in BP was observed in subjects with AN after therapeutic doses of subcutaneous insulin closely mimicking the conditions of the real life of diabetic subjects. In subjects with intact SNS, the first hemodynamic effect overrides the second, and BP does not change or tends to increase.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations